Study guides

☆☆

Q: What is X plus 0 plus 13?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

x2 + 2x - 13 = 2 x2 + 2x - 15 = 0 (x + 5)(x - 3) = 0 x + 5 = 0 and x - 3 = 0 so x = -5 and x = 3

x2+26x = 68 x2+26x-68 = 0 (x+13)2-68 = 0 (x+13)2-169-68 = 0 x+13 = +/- the square root of 237 x = -13 +/- the square root of 237

If (x + 3)(x +7) = 0 then either: x + 3 = 0 or x + 7 = 7 Hence x = -3 or -7.

x = 13

Related questions

x2+12x-13=0 The factor of x2+12x-13 is: (x+13)(x-1) So: x+13 = 0 or x-1 = 0 The answer is: x=-13 or x=1

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

= 18x + 13

x2 + 2x - 13 = 2 x2 + 2x - 15 = 0 (x + 5)(x - 3) = 0 x + 5 = 0 and x - 3 = 0 so x = -5 and x = 3

x + 12x - 45 = 0 13x - 45 = 0 13x = -45 x = - 45/13 = -3.462 (rounded)

4x2 - 13 x + 3 = 0 (4x - 1)(x - 3) = 0 x = 3, 1/4

0 = -925000 + 60000/13 - x Add x to both sides: x = -925000 + 60000/13 Simplify the Right Hand Side: x = -12085000/13 = -929615.3846, approx.

8(1+5x) +5 = 13+5x => 8+40x + 5 = 13 +5x => 13+40x = 13+5x => 13-13+40x = 13-13+5x => 40x = 5x => 40x - 5x = 0 => 35x = 0 => 35x/35 = 0/35 => x = 0

x = 256.5(-2x + 513 = 0)(x - 256.5 = 0) Divide both sides by -2(x = 256.5) Multiply by negative

x2+26x = 68 x2+26x-68 = 0 (x+13)2-68 = 0 (x+13)2-169-68 = 0 x+13 = +/- the square root of 237 x = -13 +/- the square root of 237

x = 0

-x2 + 11x + 26 = -(x - 13)(x + 2) = (13 - x)(x + 2) = (x - 13)(-x - 2)

People also asked